Pragmatic Contributions to the Implementation of the New Code of Criminal Procedure - Ruesta, Yon (2010)
This paper develops the main pragmatic contributions brought by the implementation of the new Criminal Procedure Code. It also analyzes the problems regarding its implementation. The model that preceded the criminal procedure reform was a model of inquisitive process, where the judge was the main actor. With the arrival of the new Code of Criminal Procedure, the role of prosecutors and the Public Ministry acquires greater relevance, being these the ones in charge of the investigation in its entirety. The author establishes the following as contributions of the new Criminal Procedure Code: i) the interdiction of multiple criminal prosecution, ii) the delimitation of the performance of justice operators, iii) the functions of the National Police of Peru are established, iv ) the delimitation of jurisdictional bodies, v) the regulation of procedural costs and vi) establishes a new regulation regarding international judicial cooperation. On the other hand, the author develops the problem regarding the implementation of the new Code of Criminal Procedure. Among the general aspects, two points can be seen, the first, referring to the reform's budgets and the second, to the facts of the reform. With respect to the first, the criminal procedure reform presupposes judicial independence for its implementation; however, this will only be possible if there are legal applicants who make fair decisions. Regarding the second, very apart from the changes proposed by the reform, a change of mentality is necessary. For this change to happen, the deficiencies and deficiencies of the justice operators must be overcome, these deficiencies can be of all kinds, academic, economic, training, etc. Following this line, among the specific aspects, the author develops three major problems: i) the incorporation of experts to the staff of the prosecutor in charge of the preparatory investigation, ii) the oral trial and iii) the early entry into force of the new Code of Criminal Procedure.